2007
DOI: 10.1161/01.res.0000253094.03023.3f
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Endothelial Proliferation Requires Both mTORC1 and mTORC2

Abstract: Abstract-A central regulator of cell growth that has been implicated in responses to stress such as hypoxia is mTOR (mammalian Target Of Rapamycin). We have shown previously that mTOR is required for angiogenesis in vitro and endothelial cell proliferation in response to hypoxia. Here we have investigated mTOR-associated signaling components under hypoxia and their effects on cell proliferation in rat aortic endothelial cells (RAECs). Hypoxia (1% O 2 ) rapidly (Ͼ30 minutes) and in a concentration-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 46 publications
6
113
0
3
Order By: Relevance
“…MHC class I ligation lead to the phosphorylation of several downstream targets of mTORC1 signaling, including S6K at Thr 389 , S6RP at Ser 235/236 , and 4E-BP1 at Thr 37/46 and the mTORC2 signaling target Akt at Ser 473 . These effects were consistent with previous findings showing that mTORC1 and mTORC2 complexes preceded activation of S6K at Thr 389 and Akt at Ser 473 , respectively, in a model of hypoxia-induced endothelial cell proliferation (37). Furthermore, we show for the first time that MHC class I ligation led to an increase in both mTORC1 and mTORC2 formation following 10 min of stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…MHC class I ligation lead to the phosphorylation of several downstream targets of mTORC1 signaling, including S6K at Thr 389 , S6RP at Ser 235/236 , and 4E-BP1 at Thr 37/46 and the mTORC2 signaling target Akt at Ser 473 . These effects were consistent with previous findings showing that mTORC1 and mTORC2 complexes preceded activation of S6K at Thr 389 and Akt at Ser 473 , respectively, in a model of hypoxia-induced endothelial cell proliferation (37). Furthermore, we show for the first time that MHC class I ligation led to an increase in both mTORC1 and mTORC2 formation following 10 min of stimulation.…”
Section: Discussionsupporting
confidence: 93%
“…mTOR exists in two complexes in cells: mTORC1 and mTORC2, both of which are required for endothelial cell proliferation. In pathological angiogenesis, mTORC1 mediates an earlier and transient response, whereas mTORC2's effect is more sustained (37). In endothelial cells, rapamycin could not only inhibit mTORC1 but inhibit mTORC2 after long incubation because of its disruption of mTORC2 assembly (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al demonstrated that 15(S)-hydroxyeicosatetraenoic acid activates the PI3K / Akt/ mTOR / p70S6K pathway and activation of this pathway induces tube formation and migration of human dermal microvascular ECs in vitro and Matrigel plug angiogenesis in vivo (32). In addition, Li and coworkers showed that hypoxia-induced rAEC proliferation requires mTORC1 signaling (33). These observations indicate that the mTOR signaling pathway plays an important role in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%